2005
DOI: 10.1016/j.mehy.2005.01.026
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptophan plus SSRIs for interferon-induced depression: Synergistic mechanisms for normalizing synaptic serotonin

Abstract: Summary Interferon-a (IFN) is widely used in the treatment of certain cancers and viral infections, including hepatitis C (HCV). Unfortunately, depression is a common side effect of IFN therapy, affecting approximately a third of HCV patients receiving IFN therapy. Studies have shown that selective serotonin reuptake inhibitors (SSRIs) can effectively treat IFN-induced depression in only 63-75% of cases. For the remaining percentage, depression often necessitates dose reduction of or discontinuation from IFN t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 44 publications
(38 reference statements)
0
18
0
1
Order By: Relevance
“…In particular, exogenous administration of IFN-a has been shown to cause depression in some patients (Musselman et al, 2001;Hauser et al, 2002;Loftis & Hauser, 2004). This IFN-induced depression has been attributed to the activation of the cytokine network (i.e., IFN-g) and IDO, resulting in perturbations of the serotonergic system (Menkes & MacDonald, 2000;Bonaccorso et al, 2002;Capuron et al, 2003;Turner & Blackwell, 2005). In agreement with these findings, IFN-a treatment increases the kynurenine-to-tryptophan ratio, which estimates the activity of IDO, suggesting potentiated 5-HTP and serotonin catabolism (Bonaccorso et al, 2002).…”
Section: Factors Affecting 5-hydroxytryptophan Availability For Serotmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, exogenous administration of IFN-a has been shown to cause depression in some patients (Musselman et al, 2001;Hauser et al, 2002;Loftis & Hauser, 2004). This IFN-induced depression has been attributed to the activation of the cytokine network (i.e., IFN-g) and IDO, resulting in perturbations of the serotonergic system (Menkes & MacDonald, 2000;Bonaccorso et al, 2002;Capuron et al, 2003;Turner & Blackwell, 2005). In agreement with these findings, IFN-a treatment increases the kynurenine-to-tryptophan ratio, which estimates the activity of IDO, suggesting potentiated 5-HTP and serotonin catabolism (Bonaccorso et al, 2002).…”
Section: Factors Affecting 5-hydroxytryptophan Availability For Serotmentioning
confidence: 99%
“…Thus, IFN-a may induce depression by a serotonergic-related mechanism (Schaefer et al, 2003;Wichers & Maes, 2004). To the extent that this is the mechanism for IFN-induced depression, it should be treatable with exogenous 5-HTP (Menkes & MacDonald, 2000;Turner & Blackwell, 2005).…”
Section: Factors Affecting 5-hydroxytryptophan Availability For Serotmentioning
confidence: 99%
“…Other workers have also reported similar high success rates in the treatment of depression following INF- therapy, with Turner and Blackwell (2005) reporting effective response in up to 75% and Lang et al 78.5% (2003). Both Schramm et al (2000) and Hauser (2004) also reported almost 100% success in their series.…”
Section: Discussionmentioning
confidence: 68%
“…The fact that SSRIs sometimes are not efficacious, especially in a prophylactic role, can probably be explained by the fact that IFN not only increases serotonin re-uptake but also decreases serotonin synthesis. 85 Overall, more studies are needed to establish the role of SSRIs and SNRIs in the prevention and treatment of depression and their effectiveness in compliance and SVR rates. Psychiatric evaluation is mandatory when suicidal ideation becomes evident and treatment should be discontinued in such cases.…”
Section: Discussionmentioning
confidence: 99%